Identifying Homeless Medicaid Enrollees Using Enrollment Addresses. (3rd July 2017) - Vickery, Katherine D.; Shippee, Nathan D.; Bodurtha, Peter; Guzman‐Corrales, Laura M.; Reamer, Elyse; Soderlund, Dana; Abel, Stephanie; Robertshaw, Danielle; Gelberg, Lillian
Abstract : Objective: To design and test the validity of a method to identify homelessness among Medicaid enrollees using mailing address data. Data Sources/Study Setting: Enrollment and claims data on Medicaid expansion enrollees in Hennepin and Ramsey counties who also provided self‐reported information on their current housing situation in a psychosocial needs assessment. Study Design: Construction of address‐based indicators and comparison with self‐report data. Principal Findings: Among 1, 677 enrollees, 427 (25 percent) self‐reported homelessness, of whom 328 (77 percent) had at least one positive address indicator. Depending on the type of addresses included in the indicator, sensitivity to detect self‐reported homelessness ranged from 30 to 76 percent and specificity from 79 to 97 percent. Conclusions: An address‐based indicator can identify a large proportion of Medicaid enrollees who are experiencing homelessness. This approach may be of interest to researchers, states, and health systems attempting to identify homeless populations.